Some aspects of winter wheat productivity - M. V. Kuzenko (Новые технологии)
The article presents studies carried out in 2018–2019 and 2019–2020 in the southern foothill zone of the North-West Caucasus in the fields of the selection and primary seed produc- tion department of the Adygh Research Institute of Agriculture. The aim was to study the actual, biological or potential yield of winter soft wheat varieties cultivated in the region, as well as the ratio of the mass of the grain part and the harvested straw - the yield index. The studied varieties were divided into groups according to plant height: semi-dwarfs (up to 90 cm), short-stemmed (up to 105 cm), medium-sized (up to 120 cm). According to the results of the studies carried out, differences in the studied characteristics were revealed. In the group of semi-dwarf varieties, the grain yield varied from 7,25 to 8,05 t/ha, short-stemmed 7,78–8,91 t/ha, medium-sized 7,34–9,60 t/ha. The highest grain yield was shown by the Vekha variety (9,60 t/ha) belonging to the group of medium-sized varieties, from the short-stemmed Maikopchanka varieties (8,91 t/ha) stood out, Kalym semi-dwarf varieties (8,05 t/ha). The biological yield in the experiment varied from 9,37 to 15,29 t/ha. From semi-dwarf varieties, Grom stood out (14,06 t/ha), short-stemmed varieties – Mafe (10,8 t/ha), medium-sized varieties – Vekha (15,29 t/ha). The difference between the actual and biological grain yield of varieties belonging to the short-stem group was the smallest in comparison with the varieties of the semi-dwarf and medium-grown group. On average, over two years of research, the harvesting index was 46,9–53,2%. Semi-dwarf winter wheat varieties had the maximum value of this indicator. In the group of short-stemmed Grom and Graf varieties, the ratio of the mass of the grain part to the harvested straw varied from 46,8% (Velena) to 50,5% (Alekseich). The harvesting index for medium-sized varieties was at the level of 46,9–51,8%. The Vekha variety, which showed the maximum value, stood out from this group.